Approaches to crime control and order maintenance in transitional societies: the role of village headmen, chiefs, sub-chiefs and administration police in rural Kenya - Mbuba, Jospeter M. (African journal of criminology and justice studies, 2011)
The need to illuminate and contextualize approaches to crime control and order maintenance in transitional societies has become increasingly necessary, thanks to the pervasiveness of social disorder and the elusive nature of crime in general. This study focuses on the functions of the Provincial Administration and the Administration Police in Kenya in order to reveal the little known but overarching powers of Chiefs and Sub-Chiefs as the official agents of crime control and order maintenance in the rural parts of the country. The study, which is a culmination of an in-depth review of Kenya’s legal framework and other germane literature, uses the country to cast a thoughtful appraisal of the African experience and, as a result, to provide a strong and reliable data point that could be used in cross-cultural and comparative crime control studies.